2021
DOI: 10.1186/s40001-021-00546-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors of PICC-related bloodstream infection in newborns: implications for nursing care

Abstract: Background It is necessary to analyze the characteristics and risk factors of catheter-related bloodstream infection (CRBSI) in newborns with peripherally inserted central catheter (PICC). Methods Newborns undergoing PICC catheterization in the neonatal department of our hospital from January 1, 2020 to January 31, 2021 were included. The characteristics of newborns with and without CRBSI newborns were compared and analyzed. Logistic regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…With the widespread use of peripheral central venous cannulae in the treatment of cancer patients, it has been found that complications from PICC-induced bloodstream infections are gradually gaining the attention of physicians and patients [ 9 ]. Once a bloodstream infection is formed, it will inevitably increase the physical and mental burden of the patient and at the same time reduce the initiative and motivation of the patient, which ultimately affects the prognosis to a great extent [ 10 ]. Relevant research data show that the mortality rate of bloodstream infections due to PICC is about 11.6% [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the widespread use of peripheral central venous cannulae in the treatment of cancer patients, it has been found that complications from PICC-induced bloodstream infections are gradually gaining the attention of physicians and patients [ 9 ]. Once a bloodstream infection is formed, it will inevitably increase the physical and mental burden of the patient and at the same time reduce the initiative and motivation of the patient, which ultimately affects the prognosis to a great extent [ 10 ]. Relevant research data show that the mortality rate of bloodstream infections due to PICC is about 11.6% [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the PICC provides the mainstay of long-term, International Journal of Pediatrics stable venous access, its complications remain a concern. Peripherally inserted central catheter is associated with increased risks of catheter-related bloodstream infection [72], thrombosis [73,74], extravasation and intrahepatic collections of hyperalimentation [75], massive consolidation of the upper lobes of both lungs [76], and plural effusion [77].…”
Section: Complications Of Peripherally Inserted Central Cathetermentioning
confidence: 99%
“…Although the PICC provides the mainstay of long-term, stable venous access, its complications remain a concern. Peripherally inserted central catheter is associated with increased risks of catheter-related bloodstream infection [ 72 ], thrombosis [ 73 , 74 ], extravasation and intrahepatic collections of hyperalimentation [ 75 ], massive consolidation of the upper lobes of both lungs [ 76 ], and plural effusion [ 77 ]. From the unusual complications of PICC, an embolism of fragment of the catheter tip into the peripheral branch of the left pulmonary artery, perforation of the pulmonary artery peripheral branch [ 78 ], focal neurological manifestations in a form of tonic-clonic movement of the lower limb induced by inadvertent placement of PICC in the ascending lumber vein [ 79 ], oliguria due to malposition of the catheter tip into the renal vein with a subsequent vein occlusion or renal damage by solutions administered through the renal vein [ 80 ], cardiac arrythmia [ 81 ], cardiac tamponade, and death [ 82 , 83 ].…”
Section: Percutaneous Central Venous Catheterization (Peripherally In...mentioning
confidence: 99%
“…System development environment (SDE) is an application software used in response to the engineering development and maintenance of application software and system software based on basic hardware and digital software, which is called SDE. SDE is composed of software tools and environment integration mechanism [16,17]. Software tools are used to support software R & D processes, tasks, and activities.…”
Section: System Development Environment Designmentioning
confidence: 99%